1950
DOI: 10.1149/1.2777898
|View full text |Cite
|
Sign up to set email alerts
|

The Fluorescence of Magnesium Germanate Activated by Manganese

Abstract: Magnesium germanate activated by manganese may contain the activator in different valencies. When this valency is higher than two, fluorescence excited by ultraviolet occurs in seven narrow bands decaying with the same time constant. The variation of this decay constant and the intensity of fluorescence with temperature is explained by the assumption that the relative contribution of radiative and nonradiative transitions is determined by a Boltzmann equilibrium regulating the population of various excited sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1951
1951
1970
1970

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…The second illustrative case, where thermal equilibrium exists between the populations of the various excited levels, has been discussed in considerable detail by Kroeger and van den Boomgaard (22). If the equilibrium involves a Boltzmann distribution, then the decay of the fluorescence starting from each of our two assumed levels is identical and is given by g171 + g272e -~tkr gl + g2e -'tkr…”
Section: = (~Oe--~/ktmentioning
confidence: 99%
See 1 more Smart Citation
“…The second illustrative case, where thermal equilibrium exists between the populations of the various excited levels, has been discussed in considerable detail by Kroeger and van den Boomgaard (22). If the equilibrium involves a Boltzmann distribution, then the decay of the fluorescence starting from each of our two assumed levels is identical and is given by g171 + g272e -~tkr gl + g2e -'tkr…”
Section: = (~Oe--~/ktmentioning
confidence: 99%
“…The second illustrative case, where thermal equilibrium exists between the populations of the various excited levels, has been discussed in considerable detail by Kroeger and van den Boomgaard (22). If the equilibrium involves a Boltzmann distribution, then the decay of the fluorescence starting from each of our two assumed levels is identical and is given by g171 + g272e -~tkr gl + g2e -'tkr Here gl and g: indicate the statistical weights of the levels 1 and 2 while ~,~ and ~,: indicate the transition probabilities of the fluorescence transitions starting from these levels, e is the energy difference between the two levels.…”
Section: = (~Oe--~/ktmentioning
confidence: 99%
“…If ir is assumed that there is a real difference between the two phosphor groups this would be supported by KROEGER'S and VAN DEN BOOMGARD'S [9] observations on the temperature dependence of the sub-bands of magnesium germanate, which indicate a subdivision in characteristics at about 6400 ~ ~.…”
Section: Discussionmentioning
confidence: 81%
“…A number of other phosphors, activated with tetravalent manganese, also follow the general pattern of the new phosphors described above. These include magnesium titanate, ~-alumina, magnesium aluminate and strontium aluminate [9]. KROEGER [1] has shown that annealed magnesium titanate has a main emission band at about 6600/~ which resolves into a finer structure at --180 ~ C while the spectrum of a quenched product gives a similar but more diffuse spectrum.…”
Section: Characteristics Of Tetravalent Manganese Activated Phosphorsmentioning
confidence: 99%